Hand posture effects on handedness recognition as revealed by the Simon effect - Lameira, Allan P.; Gawryszewski, Luiz G.; Silva, Sabrina G.; Ferreira, Fernanda M.; Vargas, Claudia; Umilta, Carlo; Pereira, Antonio (Frontiers in Human Neuroscience, 2009)
We investigated the influence of hand posture in handedness recognition, while varying the spatial correspondence between stimulus and response in a modified Simon task. Drawings of the left and right hands were displayed either in a back or palm view while participants discriminated stimulus handedness by pressing left/right keys with their hands resting either in a prone or supine posture. As a control, subjects performed a regular Simon task using simple geometric shapes as stimuli. Results showed that when hands were in a prone posture, the spatially corresponding trials (i.e., stimulus and response located on the same side) were faster than the non-corresponding trials (i.e., stimulus and response on opposite sides). In contrast, for the supine posture, there was no difference between corresponding and non-corresponding trials. The control experiment with the regular Simon task showed that the posture of the responding hand had no influence on performance. When the stimulus is the drawing of a hand, however, the posture of the responding hand affects the spatial correspondence effect because response location is coded based on multiple reference points, including the body of the hand.